Maternal Vaccination and Risk of Hospitalization for Covid-19 Among Infants. Issue 1 (January 2023) - Halasa, Natasha B.; Olson, Samantha M.; Staat, Mary A.; Newhams, Margaret M.; Price, Ashley M.; Pannaraj, Pia S.; Boom, Julie A.; Sahni, Leila C.; Chiotos, Kathleen; Cameron, Melissa A.; Bline, Katherine E.; Hobbs, Charlotte V.; et al.
Abstract : (Abstracted from N Engl J Med 2022;387:109–119) COVID-19 during pregnancy is associated with a greater risk of adverse pregnancy outcomes and neonatal complications. Studies have shown that mRNA vaccines are highly effective in preventing severe COVID-19 during pregnancy, and the Centers for Disease Control and Prevention recommends vaccination, including boosters, for people who are pregnant or plan to be pregnant.